Wave-pipelined multiplexed (WPM) routing for gigascale integration (GSI). - Joshi, A.J (IEEE Transactions on VLSI systems)
In modern-day VLSI systems, performance and manufacturing costs are being driven by the on-chip wiring needs due to the continuous increase in the number of transistors. This paper proposes a low overhead wave-pipelined multiplexed (WPM) routing technique that harnesses the inherent intraclock period interconnect idleness to implement wire sharing throughout the various hierarchical levels of design. It is illustrated in this paper that the WPM network can be readily incorporated into future gigascale integration (GSI) systems to reduce the number of interconnect routing channels in an attempt to contain escalating manufacturing costs. Both, a system level analysis and circuit level verification of this WPM routing are presented in this paper. A multilevel interconnect network design simulator (MINDS) that uses system level interconnect prediction (SLIP) techniques and HSPICE circuit simulations for optimizing the interconnect dimensions has been used to assess the opportunities for application of WPM wire circuits in high performance digital designs. A custom routing example highlights the ease with which the WPM routing technique can be easily incorporated into the existing VLSI systems. In addition, for a 40 million transistor system case study, this system level analysis reveals that the use of a WPM network could result in an almost 20% decrease in the number of metal layers for less than 4% increase in dynamic power with no loss of communication throughput performance. The key virtues of WPM routing are its flexibility, robustness, implementation simplicity and its low overhead requirements.